UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR FISIKAMELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) PADA SISWA KELAS XI IPA 3 DI SMAN 3 JEMBER - Khotimatul Huznia; Subiki Subiki; Rayendra Wahyu Bachtiar (FKIP Universitas Jember, 2018)
Abstract The research aimed to improved the learning activity and learning outcomes ofcognitive students about the concept of physics with cooperative learning model typethink pair share in students grade XI IPA 3 SMAN 3 Jember in the lesson of 2017/2018,with 34 students. The type of research was classroom action research. The research consisted two cycles, began with the initial activity cycle. The result of the research wasanalyzed descriptively consisted of two indicators such as learning activity and learningoutcomes research. The learning activity of student got average value on cycle I equal to52% which enter in category enough active and at second cycle equal to 77% included inactive category. While for the study results obtained from the average score for the firstcycle of 67 in the category enough and the second cycle of 77 included in either categorywith 80% completeness. It can be concluded that the application of type of cooperativelearning model type Think pair share (TPS) can increase student activity and learningoutcomes about physics class XI IPA 3 SMAN 3 Jember.Keywords: Activity of Learrning, Cooperative Think Pair Share (TPS), Results of learning